(untitled) (Papeles, 2023)
Introduction: After the implementation of the European Higher Education Area (EHEA), modules on foreign languages (especially, English) gained importance through a series of changes introduced in the curriculum in the framework of the new Bolonia Process, motivated as well by the Common European Framework of Reference for Languages (CEFRL). In the case of the Degree in Early Childhood Education, the inclusion of English as a Foreign Language (EFL) modules had a very instrumental focus, concentrating on linguistic aspects of the language. Nonetheless, the competences in such EFL modules were general without taking into consideration the professional and academic needs. Methodology: Hence, the aim of this work is to identify tendencies in the EFL modules in the Degrees in Early Childhood Education. With a convenience sample of 10 Spanish state universities, their Academic Guides were analyzed using an ad hoc instrument based on Garcés (2021a). Results and conclusion: The results obtained demonstrated a balance between specific context on education, and language-related aspects, with a certain degree of variation between the items analyzed.